Tubercular Cervical Lymphadenopathy Clinicopathological Study of Thirty Cases - Biswas, P Kumar; Begum, SMK Nahar (TAJ: Journal of Teachers Association, 2009)
A clinico-pathological study of tuberculosis in cervical lymph nodes was carried out among 30 cases irrespective of age and sex. Tuberculosis was common in adolescent and young adult life (63.3%). It was more prevalent in female (63.4%) and in poor socioeconomic condition (60%). Most of the cases were non-vaccinated (70%) and majority (70%) was tuberculin positive. doi: 10.3329/taj.v20i1.3087 TAJ 2007; 20(1): 36-38